Doped and modified LiAl-LDH as well as preparation method and application thereof
By introducing doping elements into LiAl-LDH and adopting co-precipitation method and crystallization treatment, the problem of low adsorption efficiency of existing aluminum-type lithium ion sieves in high sulfate environments is solved, and more efficient and stable lithium is achieved Ion adsorption effect.
Patent Information
- Application Number
- CN202411571435.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The adsorption efficiency of existing aluminum-based lithium-ion sieves in brine with high sulfate content is reduced, and the structure is easily damaged, resulting in a significant reduction in the desorption amount of lithium ion.
By introducing doped elements Zn, Ce, Mn, Fe, Ca, La and Ni into LiAl-LDH, the charge distribution and pore structure inside are adjusted, and the resistance to sulfate ions is enhanced, and the co-precipitation method and crystallization are used to regulate their internal charge distribution and pore structure, so as to enhance their resistance to sulfate ions. Chemical treatment improves crystallinity and adsorption performance.
The adsorption capacity and selectivity of lithium ions are significantly improved, the degree of poisoning of adsorbents in high sulfate content brines is reduced, and a more efficient and stable lithium extraction process in salt lakes is achieved.
Smart Images

Figure CN119430265A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion sieves, and in particular to a doped and modified LiAl-LDH and a preparation method and application thereof. Background Art
[0002] With the vigorous development of the new energy industry, the demand for lithium resources continues to rise, becoming a key raw material for the global energy transformation. In this context, salt lake lithium extraction technology has attracted attention due to its wide distribution of resources, especially in my country, where lithium extraction from salt lakes has become an important way to obtain lithium resources. However, my country's salt lake resources have the characteristics of low lithium concentration, poor grade, and many coexisting ions, which put forward higher requirements for lithium extraction technology. In order to meet these challenges, adsorption + membrane coupling technology came into being, becoming the mainstream development direction and breakthrough point of future salt lake lithium extraction technology.
[0003] Among many adsorbents, aluminum-based adsorbents were the first to be industrialized due to their good lithium adsorption performance. The skeleton of aluminum-based adsorbents is composed of Al-O octahedrons sharing edges to form a main plate layer, lithium ions occupy 1 / 3 of the octahedral vacancies, and guest interlayers are inserted with anions and water molecules to balance the charge and stabilize the structure. This structure gives aluminum-based adsorbents high selectivity for lithium ions. However, in practical applications, sulfate ions are embedded in the aluminum-based lithium ion sieve interlayer through electrostatic attraction and anion exchange, which will lead to a decrease in the crystallinity of the adsorbent and partial structural collapse, thereby reducing the adsorption capacity and selectivity of the adsorbent. In addition, the strong interaction between sulfate ions and lithium ions will also lead to a significant reduction in the amount of lithium ion desorption.
[0004] Considering that the area of sulfate salt lakes in my country accounts for more than 50% of the total salt lake area, developing an adsorbent that can resist or inhibit sulfate poisoning is crucial to improving the efficiency of lithium extraction from salt lakes.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the objectives of the present invention is to provide a doped modified LiAl-LDH, aiming to solve at least one of the above technical problems in the prior art.
[0007] A second object of the present invention is to provide a method for preparing doped modified LiAl-LDH.
[0008] A third object of the present invention is to provide an application of doped modified LiAl-LDH.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] The first aspect of the present invention provides a doped modified LiAl-LDH having a molecular formula of M x ·LiCl y ·2Al(OH) 3 ·nH 2 O;
[0011] Wherein, M is at least one of Zn, Ce, Mn, Fe, Ca, La and Ni;
[0012] The value of x is 0.005~0.01; the value of y is 0.5~1.5; the value of n is 0~6.
[0013] The second aspect of the present invention provides a method for preparing the doped modified LiAl-LDH, comprising the following steps:
[0014] A. mixing an aluminum source solution, a lithium source solution and an M source solution to obtain a mixed solution; adjusting the pH of the mixed solution to 5 to 10, and performing a coprecipitation reaction;
[0015] B. After the coprecipitation reaction is completed, the slurry is transferred to a reactor for crystallization treatment, and finally filtered, washed, dried and crushed to obtain the doped modified LiAl-LDH.
[0016] Furthermore, the aluminum source is a soluble aluminum salt.
[0017] Preferably, the soluble aluminum salt comprises at least one of sulfate, aluminum nitrate and aluminum chloride.
[0018] Preferably, the lithium source includes at least one of lithium sulfate, lithium carbonate, lithium nitrate, lithium chloride and lithium hydroxide.
[0019] Preferably, the M source comprises a soluble salt containing the M element.
[0020] Furthermore, the mixing temperature is 50-90°C.
[0021] Preferably, the coprecipitation reaction time is 2 to 8 hours.
[0022] Preferably, the crystallization treatment is performed at a temperature of 90 to 200° C. and for a time of 8 to 48 hours.
[0023] Furthermore, in the mixed solution, the molar ratio of aluminum element to lithium element is 0.5 to 3:1.
[0024] Preferably, in the mixed solution, the total concentration of the aluminum source and the lithium source is 0.5 to 10 mol / L.
[0025] Preferably, in the mixed solution, the M source accounts for 0.1 to 50% of the total mass of the aluminum source and the lithium source.
[0026] Preferably, the crystallization treatment is performed at a temperature of 100 to 180° C. and for a time of 12 to 48 hours.
[0027] The third aspect of the present invention provides the use of the doped modified LiAl-LDH in lithium extraction from salt lakes.
[0028] Compared with the prior art, the present invention has at least the following beneficial effects:
[0029] The doped modified LiAl-LDH provided by the present invention introduces at least one of the doping elements Zn, Ce, Mn, Fe, Ca, La and Ni into the layered structure of LiAl-LDH, adjusts the charge distribution and pore structure inside LiAl-LDH, enhances the ability of the adsorbent to resist sulfate ions, prevents sulfate ions from being embedded in the interlayer and causing the adsorbent structure to be destroyed, thereby ensuring that the adsorbent can still maintain a high adsorption efficiency in brine with a high sulfate content. In addition, the doping element changes the electronic structure inside LiAl-LDH, reduces the Li + The diffusion energy barrier in LiAl-LDH is reduced, thereby improving the adsorption performance of LiAl-LDH.
[0030] The preparation method provided by the present invention adopts a coprecipitation method to prepare doped and modified LiAl-LDH, which is simple to operate, easy to scale up production, has high process controllability, improves product quality and consistency, and is conducive to industrial application.
[0031] The application of the doped modified LiAl-LDH provided by the present invention provides a lithium ion sieve with better performance for lithium extraction from salt lakes, especially for lithium extraction from sulfate-type salt lakes, significantly improves the adsorption capacity and selectivity of lithium ions, thereby reducing the degree of poisoning of the adsorbent in brine with high sulfate content, and realizing a more efficient and stable lithium extraction process from salt lakes. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a scanning electron microscope image of the Ce-doped modified LiAl-LDH provided in Example 1;
[0034] Figure 2 A scanning electron microscope image of Ce-doped modified LiAl-LDH provided in Example 2;
[0035] Figure 3 A scanning electron microscope image of the Mn-doped modified LiAl-LDH provided in Example 3;
[0036] Figure 4 A scanning electron microscope image of the Mn-doped LiAl-LDH provided in Example 4;
[0037] Figure 5 The scanning electron microscope image of LiAl-LDH provided for Comparative Example 1;
[0038] Figure 6 XRD pattern provided for characterization example 2. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0040] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.
[0041] The first aspect of the present invention provides a doped modified LiAl-LDH having a molecular formula of M x ·LiCl y ·2Al(OH) 3 ·nH 2 O;
[0042] Wherein, M is at least one of Zn, Ce, Mn, Fe, Ca, La and Ni;
[0043] The value of x is 0.005~0.01; the value of y is 0.5~1.5; the value of n is 0~6.
[0044] The doped modified LiAl-LDH provided by the present invention introduces at least one of the doping elements Zn, Ce, Mn, Fe, Ca, La and Ni into the layered structure of LiAl-LDH, adjusts the charge distribution and pore structure inside LiAl-LDH, enhances the ability of the adsorbent to resist sulfate ions, prevents sulfate ions from being embedded in the interlayer and causing the adsorbent structure to be destroyed, thereby ensuring that the adsorbent can still maintain a high adsorption efficiency in brine with a high sulfate content. In addition, the doping element changes the electronic structure inside LiAl-LDH, reduces the Li + The diffusion energy barrier in LiAl-LDH is reduced, thereby improving the adsorption performance of LiAl-LDH.
[0045] Typically but not limiting, the value of x can be 0.005, 0.006, 0.007, 0.008, 0.009 or 0.01, or any value in the range of 0.005 to 0.01; the value of y can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5, or any value in the range of 0.5 to 1.5; the value of n can be 0, 1, 2, 3, 4, 5 or 6, or any value in the range of 0 to 6.
[0046] The second aspect of the present invention provides a method for preparing the doped modified LiAl-LDH, comprising the following steps:
[0047] A. mixing an aluminum source solution, a lithium source solution and an M source solution to obtain a mixed solution; adjusting the pH of the mixed solution to 5 to 10, and performing a coprecipitation reaction;
[0048] B. After the coprecipitation reaction is completed, the slurry is transferred to a reactor for crystallization treatment, and finally filtered, washed, dried and crushed to obtain the doped modified LiAl-LDH.
[0049] The preparation method provided by the present invention adopts a coprecipitation method to prepare doped and modified LiAl-LDH, which is simple to operate, easy to scale up production, has high process controllability, improves product quality and consistency, and is conducive to industrial application.
[0050] Furthermore, the aluminum source is a soluble aluminum salt.
[0051] Preferably, the soluble aluminum salt comprises at least one of aluminum sulfate, aluminum nitrate and aluminum chloride.
[0052] Preferably, the lithium source includes at least one of lithium sulfate, lithium carbonate, lithium nitrate, lithium chloride and lithium hydroxide.
[0053] Preferably, the M source comprises a soluble salt containing the M element.
[0054] Specifically, when M is Zn, the soluble salt containing the Zn element includes at least one of zinc nitrate, zinc sulfate and zinc chloride; when M is Ce, the soluble salt containing the Ce element includes cerium nitrate and cerium chloride; when M is Mn, the soluble salt containing the Mn element includes at least one of manganese nitrate, manganese sulfate and manganese chloride; when M is Fe, the soluble salt containing the Fe element includes at least one of ferric nitrate, ferric sulfate, ferric chloride, ferrous nitrate, ferrous sulfate and ferrous chloride; when M is Ca, the soluble salt containing the Ca element includes calcium nitrate and calcium chloride; when M is La, the soluble salt containing the La element includes lanthanum nitrate and lanthanum chloride; when M is Ni, the soluble salt containing the Ni element includes at least one of nickel nitrate, nickel sulfate and nickel chloride.
[0055] Furthermore, the mixing temperature is 50-90°C.
[0056] Typically but not limiting, the temperature of the mixing process can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, or any value within the range of 50°C to 90°C.
[0057] Preferably, the coprecipitation reaction time is 2 to 8 hours.
[0058] Typically but not limiting, the coprecipitation reaction time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, or any value within the range of 2 hours to 8 hours.
[0059] Preferably, the crystallization treatment is performed at a temperature of 90 to 200° C. and for a time of 8 to 48 hours.
[0060] The crystallization treatment improves the crystallinity of the doped LiAl-LDH, making the crystal structure more complete and ordered, which is crucial for the adsorption performance of the doped LiAl-LDH, because the highly ordered crystal structure can provide more active sites, thereby enhancing the adsorption capacity and selectivity for lithium ions. With the increase in crystallinity, the thermal stability of the doped LiAl-LDH is also enhanced, which enables the doped LiAl-LDH to maintain the stability of its structure and performance in a high temperature environment, especially in the process of lithium extraction from salt lakes, this feature is particularly important, because the stability under high temperature conditions ensures that the material can work effectively for a long time under harsh operating conditions.
[0061] The crystallization treatment also optimizes the pore structure and specific surface area of the material by adjusting the crystallization temperature and time, further improving the adsorption performance of the doped modified LiAl-LDH and increasing the adsorption capacity and selectivity for lithium ions. This optimized pore structure provides more adsorption sites for lithium ions and also promotes the ion transmission efficiency. In addition, the crystallization treatment enhances the structural stability of the doped modified LiAl-LDH, so that it exhibits good cycle stability during adsorption and desorption. The doped modified LiAl-LDH can maintain its performance unchanged during multiple cycles, reducing the frequency of replacement and reducing long-term operating costs.
[0062] The crystallization treatment also improves the mechanical strength of the material by refining the grains. The fine grains and increased grain boundaries increase the places where dislocations are blocked, thereby improving the overall strength of the material and making the material more durable in practical applications. The crystallization treatment optimizes the electronic structure of LiAl-LDH by doping with different metal ions and changes the electronegativity of the material, which further improves the material's ability to adsorb lithium ions. The optimized electronic structure helps to reduce the diffusion barrier of lithium ions in the material and improve the adsorption kinetics.
[0063] Typically but not limiting, the temperature of the crystallization treatment can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or 200°C, or any value in the range of 90°C to 200°C, and the time of the crystallization treatment can be 8 hours, 12 hours, 16 hours, 24 hours, 32 hours or 48 hours, or any value in the range of 8 hours to 48 hours.
[0064] Furthermore, in the mixed solution, the molar ratio of aluminum element to lithium element is 0.5 to 3:1.
[0065] Typically but not limiting, in the mixed solution, the molar ratio of aluminum element to lithium element can be 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, or any value within the range of 0.5 to 3:1.
[0066] Preferably, in the mixed solution, the total concentration of the aluminum source and the lithium source is 0.5 to 10 mol / L.
[0067] Typically but not limiting, the total concentration of the aluminum source and the lithium source in the mixed solution can be 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L, or it can be any value within the range of 0.5 mol / L to 10 mol / L.
[0068] Preferably, in the mixed solution, the M source accounts for 0.1 to 50% of the total mass of the aluminum source and the lithium source.
[0069] Typically but not limiting, in the mixed solution, the ratio of M source to the total mass of aluminum source and lithium source can be 0.1%, 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, or any value within the range of 0.1% to 50%.
[0070] Preferably, the crystallization treatment is performed at a temperature of 100 to 180° C. and for a time of 12 to 48 hours.
[0071] Typically but not limiting, the temperature of the crystallization treatment can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, or any value in the range of 100°C to 180°C, and the time of the crystallization treatment can be 12 hours, 16 hours, 20 hours, 24 hours, 28 hours, 32 hours, 36 hours, 40 hours or 48 hours, or any value in the range of 12 hours to 48 hours.
[0072] The third aspect of the present invention provides the use of the doped modified LiAl-LDH in lithium extraction from salt lakes.
[0073] The application of the doped modified LiAl-LDH provided by the present invention provides a lithium ion sieve with better performance for lithium extraction from salt lakes, especially for lithium extraction from sulfate-type salt lakes, significantly improves the adsorption capacity and selectivity of lithium ions, thereby reducing the degree of poisoning of the adsorbent in brine with high sulfate content, and realizing a more efficient and stable lithium extraction process from salt lakes.
[0074] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0075] Example 1
[0076] This embodiment provides a Ce-doped LiAl-LDH, and the preparation steps are as follows:
[0077] 1. Add aluminum nitrate, lithium nitrate and cerium nitrate to deionized water to obtain a mixed solution with concentrations of aluminum nitrate, lithium nitrate and cerium nitrate of 1.5 mol / L, 1.5 mol / L and 0.15 mol / L, respectively.
[0078] 2. Use sodium hydroxide solution to adjust the pH of the mixed solution to 8 to obtain a white precipitate, and use a constant temperature water bath to control the temperature of the mixed solution at 90° C. for 4 hours.
[0079] 3. The obtained slurry was transferred to a reactor and crystallized at 200°C for 24 hours.
[0080] 4. After the crystallization treatment, the material in the reactor was filtered, and the solid matter was washed 3 times, dried at 120°C for 8h, and finally crushed through a 100-mesh sieve to obtain Ce-doped LiAl-LDH.
[0081] Example 2
[0082] This embodiment provides a Ce-doped LiAl-LDH, and the preparation steps are as follows:
[0083] 1. Add aluminum nitrate, lithium nitrate and cerium nitrate to deionized water to obtain a mixed solution with concentrations of 3.33 mol / L, 1.67 mol / L and 0.33 mol / L of aluminum nitrate, lithium nitrate and cerium nitrate, respectively.
[0084] 2. Use sodium hydroxide solution to adjust the pH of the mixed solution to 6 to obtain a white precipitate, and use a constant temperature water bath to control the temperature of the mixed solution at 90° C. for 4 hours.
[0085] 3. The obtained slurry was transferred to a reactor and crystallized at 200°C for 12 hours.
[0086] 4. After the crystallization treatment, the material in the reactor was filtered, and the solid matter was washed 3 times, dried at 100°C for 12h, and finally crushed through a 100-mesh sieve to obtain Ce-doped LiAl-LDH.
[0087] Example 3
[0088] This embodiment provides a Mn-doped LiAl-LDH, and the preparation steps are as follows:
[0089] 1. Add aluminum chloride, lithium chloride and manganese chloride to deionized water to obtain a mixed solution with concentrations of aluminum chloride, lithium chloride and manganese chloride of 1.8 mol / L, 1.2 mol / L and 0.12 mol / L, respectively.
[0090] 2. Use sodium hydroxide solution to adjust the pH of the mixed solution to 5 to obtain a white precipitate, and use a constant temperature water bath to control the temperature of the mixed solution at 70° C. for 4 hours.
[0091] 3. The obtained slurry was transferred to a reactor and crystallized at 180°C for 12 hours.
[0092] 4. After the crystallization treatment, the material in the reactor was filtered, and the solid matter was washed 3 times, dried at 80°C for 24 hours, and finally crushed through a 100-mesh sieve to obtain Mn-doped LiAl-LDH.
[0093] Example 4
[0094] This embodiment provides a Mn-doped LiAl-LDH, and the preparation steps are as follows:
[0095] 1. Add aluminum chloride, lithium chloride and manganese chloride to deionized water to obtain a mixed solution with concentrations of aluminum chloride, lithium chloride and manganese chloride of 3.75 mol / L, 1.25 mol / L and 0.25 mol / L, respectively.
[0096] 2. Use sodium hydroxide solution to adjust the pH of the mixed solution to 8 to obtain a white precipitate, and use a constant temperature water bath to control the temperature of the mixed solution at 90° C. for 4 hours.
[0097] 3. The obtained slurry was transferred to a reactor and crystallized at 200°C for 12 hours.
[0098] 4. After the crystallization treatment, the material in the reactor was filtered, and the solid matter was washed 3 times, dried at 80°C for 12h, and finally crushed through a 100-mesh sieve to obtain Mn-doped LiAl-LDH.
[0099] Example 5
[0100] This embodiment provides a Mn and Ce doped LiAl-LDH, and the preparation steps are as follows:
[0101] 1. Add aluminum nitrate, lithium nitrate, cerium nitrate and manganese nitrate to deionized water to obtain a mixed solution with concentrations of 1.5 mol / L, 1.5 mol / L, 0.15 mol / L and 0.15 mol / L for aluminum nitrate, 1.5 mol / L for lithium nitrate, 0.15 mol / L for cerium nitrate and 0.15 mol / L for manganese nitrate, respectively.
[0102] Steps 2-4 are the same as the corresponding steps in Example 1 and will not be repeated here.
[0103] Example 6
[0104] This embodiment provides a Mn and Ce doped LiAl-LDH, and the preparation steps are as follows:
[0105] 1. Add aluminum nitrate, lithium nitrate, cerium nitrate and manganese nitrate to deionized water to obtain a mixed solution with concentrations of 1.5 mol / L, 1.5 mol / L, 0.075 mol / L and 0.075 mol / L for aluminum nitrate, 1.5 mol / L for lithium nitrate, 0.075 mol / L for cerium nitrate and 0.075 mol / L for manganese nitrate, respectively.
[0106] Steps 2-4 are the same as the corresponding steps in Example 1 and will not be repeated here.
[0107] Example 7
[0108] This embodiment provides a Ca-doped LiAl-LDH, and the preparation steps are as follows:
[0109] 1. Add aluminum nitrate, lithium nitrate and calcium nitrate to deionized water to obtain a mixed solution with concentrations of 1.5 mol / L, 1.5 mol / L and 0.15 mol / L of aluminum nitrate, lithium nitrate and calcium nitrate, respectively.
[0110] Steps 2-4 are the same as the corresponding steps in Example 1 and will not be repeated here.
[0111] Example 8
[0112] This embodiment provides a Fe-doped LiAl-LDH, and the preparation steps are as follows:
[0113] 1. Add aluminum nitrate, lithium nitrate and ferric nitrate to deionized water to obtain a mixed solution with concentrations of 1.5 mol / L, 1.5 mol / L and 0.15 mol / L of aluminum nitrate, lithium nitrate and ferric nitrate, respectively.
[0114] Steps 2-4 are the same as the corresponding steps in Example 1 and will not be repeated here.
[0115] Example 9
[0116] This embodiment provides a Ni-doped LiAl-LDH, and the preparation steps are as follows:
[0117] 1. Add aluminum nitrate, lithium nitrate and nickel nitrate to deionized water to obtain a mixed solution with concentrations of 1.5 mol / L, 1.5 mol / L and 0.15 mol / L of aluminum nitrate, lithium nitrate and nickel nitrate, respectively.
[0118] Steps 2-4 are the same as the corresponding steps in Example 1 and will not be repeated here.
[0119] Comparative Example 1
[0120] This comparative example provides a LiAl-LDH, and the preparation steps are as follows:
[0121] 1. Add aluminum nitrate and lithium nitrate to deionized water to obtain aluminum nitrate and lithium nitrate concentrations of 2.5 mol / L and 2.5 mol / L, respectively.
[0122] 2. Use sodium hydroxide solution to adjust the pH of the mixed solution to 9 to obtain a white precipitate, and use a constant temperature water bath to control the temperature of the mixed solution at 40° C. for 4 hours.
[0123] 3. The obtained slurry was transferred to a reactor and crystallized at 180°C for 12 hours.
[0124] 4. After the crystallization treatment, the material in the reactor was filtered, and the solid matter was washed 3 times, dried at 120°C for 12h, and finally crushed through a 100-mesh sieve to obtain LiAl-LDH.
[0125] Characterization Example 1
[0126] The materials obtained in Examples 1 to 4 and Comparative Example 1 were subjected to scanning electron microscopy, and the scanning electron microscopy images obtained corresponded to the following: Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 shown.
[0127] from Figure 1 It can be seen that the microscopic morphology of the material synthesized in Example 1 is a regular, tightly stacked hexagonal sheet structure. The material has a uniform morphology and good crystallization condition, indicating that the material structure is stable and has stable performance in the salt lake lithium extraction process.
[0128] from Figure 2 It can be seen that the microstructure of the material synthesized in Example 2 also has a hexagonal flake structure, but some of the structures are incomplete.
[0129] from Figure 3 It can be seen that the material synthesized in Example 3 also has a flaky structure, but there are a small number of cubic block particles in the structure, and the stacking is relatively dense, indicating that the doping of Mn requires more stringent crystallization conditions.
[0130] from Figure 4 It can be seen that the material synthesized in Example 4 has no obvious flaky structure and is mostly irregular particles, which further confirms that the crystallization conditions require a higher temperature or a longer time.
[0131] from Figure 5 It can be seen that the material synthesized in Comparative Example 1 is a hexagonal sheet structure, which is easier to achieve crystallization and structural growth without doping.
[0132] Characterization Example 2
[0133] XRD was performed on the materials obtained in Examples 1 to 4 and Comparative Example 1, and the obtained images were as follows: Figure 6 As shown. Figure 6 It can be seen that the materials synthesized in Examples 1-4 and the comparative example are all Li / Al hydrotalcite structures, corresponding to card PDF#31-0700, and there is an inorganic salt diffraction peak at around 32°, which is mainly obtained by acid-base reaction during the precipitation process.
[0134] Test Case
[0135] The materials obtained in the examples and comparative examples were tested for adsorption capacity.
[0136] The composition of simulated brine from a salt lake is shown in Table 1.
[0137] Table 1
[0138] ion <![CDATA[Mg 2+ ]]> <![CDATA[Li + ]]> <![CDATA[B 3+ ]]> <![CDATA[Ca 2+ ]]> <![CDATA[K + ]]> <![CDATA[Na + ]]> <![CDATA[SO 4 2- ]]> <![CDATA[Cl - ]]> Concentration (ppm) 25497 234.8 958 250 7975 97373 45830 219436
[0139] 1. Activation: Take 5g of the materials obtained in the embodiment and the comparative example respectively and add them into 1L of 40ppm Li + The solution was stirred in a constant temperature water bath for 0.5 h, and then vacuum filtered for solid-liquid separation. The Li + The concentration is recorded as C(Li). The activation process is completed. The obtained solid is naturally dried and used for adsorption.
[0140] 2. Adsorption: At room temperature, take 0.5g of activated aluminum lithium ion sieve powder and soak it in 100ml of laboratory prepared brine and stir continuously. Take a sample after 1 hour and test the Li + The adsorbed powder is filtered out for desorption.
[0141] 3. Analysis stage: After the adsorption is completed, the powder is dried to constant weight, 0.5 g is weighed, and 10 ml of 0-5 ° C deionized water is used to stir for 5 min, and the solid-liquid separation is filtered. Then the filtered powder is added to 200 ml of ultrapure aqueous solution, stirred and analyzed at this temperature for 2 h, and the filtrate is taken. The ion concentrations of Li, Na, K, Ca, and Mg are tested by ICP-OES inductively coupled plasma emission spectrometer and recorded as C2 (Li), C2 (Na), C2 (K), C2 (Ca), and C2 (Mg) respectively to calculate the Li resolution rate, Li / Na, Li / K, Li / Ca, and Li / Mg.
[0142] The results are shown in Table 2 below.
[0143] Table 2
[0144]
[0145] As can be seen from Table 2, the element-doped LiAl-LDH provided in Examples 1 to 9 are all conducive to improving the adsorption and desorption capacity in high-sulfuric acid salt lakes, among which Fe, Ni, and Ce have obvious improvement effects. The doping of Mn has high requirements for crystallization conditions, and the crystallization is incomplete under the same synthesis conditions, resulting in poor selectivity improvement effect compared with the above elements. The improvement effect of Ca ion doping is not obvious. This experiment confirms the lithium extraction activity of the doped LiAl-LDH, and the high desorption efficiency and stability in sulfate salt lakes.
[0146] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A doped LiAl-LDH, characterized in that: The molecular formula is M x ·LiCl y ·2Al(OH)3·nH2O; Wherein, M is at least one of Zn, Ce, Mn, Fe, Ca, La and Ni; The value of x is 0.005~0.01; the value of y is 0.5~1.5; the value of n is 0~6.
2. A method for preparing the doped modified LiAl-LDH according to claim 1, characterized in that: The following steps are involved: A. mixing an aluminum source solution, a lithium source solution and an M source solution to obtain a mixed solution; adjusting the pH of the mixed solution to 5 to 10, and performing a coprecipitation reaction; B. After the coprecipitation reaction is completed, the slurry is transferred to a reactor for crystallization treatment, and finally filtered, washed, dried and crushed to obtain the doped modified LiAl-LDH.
3. The preparation method according to claim 2, characterized in that: The aluminum source is a soluble aluminum salt; Preferably, the soluble aluminum salt comprises at least one of aluminum sulfate, aluminum nitrate and aluminum chloride; Preferably, the lithium source includes at least one of lithium sulfate, lithium carbonate, lithium nitrate, lithium chloride and lithium hydroxide; Preferably, the M source comprises a soluble salt containing the M element.
4. The preparation method according to claim 2, characterized in that: The mixing temperature is 50 to 90° C. Preferably, the coprecipitation reaction time is 2 to 8 hours; Preferably, the crystallization treatment is performed at a temperature of 90 to 200° C. and for a time of 8 to 48 hours.
5. The preparation method according to claim 2, characterized in that: In the mixed solution, the molar ratio of aluminum element to lithium element is 0.5 to 3:
1.
6. The preparation method according to claim 2, characterized in that: In the mixed solution, the total concentration of the aluminum source and the lithium source is 0.5-10 mol / L.
7. The preparation method according to claim 2, characterized in that: In the mixed solution, the M source accounts for 0.1-50% of the total mass of the aluminum source and the lithium source.
8. The preparation method according to claim 2, characterized in that: The crystallization treatment is carried out at a temperature of 100 to 180° C. and for a time of 12 to 48 hours.
9. Use of the doped modified LiAl-LDH according to claim 1 in extracting lithium from salt lakes.